The Effect of Financial Scarcity on Reinforcer Pathology: A Dyadic Developmental Examination - Amanda K. Crandall; Leonard H. Epstein; Jennifer Fillo; Kevin Carfley; Eleanor Fumerelle; Jennifer L. Temple (MDPI AG, 2022)
This study investigated the effects of experimentally manipulated scarcity on the reinforcing value of food (RRVfood) and delay discounting (DD), which, together, create reinforcer pathology (RP) among parents and offspring. A stratified sample of 106 families (53 parent/child aged 7-10 dyads & 53 parent/adolescent aged 15-17 dyads) from high- and low-income households visited our laboratory for three appointments. Each appointment included an experimental manipulation of financial gains and losses and DD and RRV tasks. The results showed that, regardless of food insecurity or condition, children had greater RP (β = 1.63, p < 0.001) than adolescents and parents. DD was largely unaffected by acute scarcity in any group, but families with food insecurity had greater DD (β = −0.09, p = 0.002) than food-secure families. Food-insecure parents with children responded to financial losses with an increase in their RRVfood (β = −0.03, p = 0.011), while food-secure parents and food-insecure parents of adolescents did not significantly change their responding based on conditions. This study replicates findings that financial losses increase the RRVfood among adults with food insecurity and extends this literature by suggesting that this is strongest for parents of children.